2015
DOI: 10.1260/1478-0771.13.3-4.257
|View full text |Cite
|
Sign up to set email alerts
|

Urban Design Synthesis for Building Layouts Based on Evolutionary Many-Criteria Optimization

Abstract: When working on urban planning projects there are usually multiple aspects to consider. Often these aspects are contradictory and it is not possible to choose one over the other; instead, they each need to be fulfilled as well as possible. In this situation ideal solutions are not always found because they are either not sought or the problems are regarded as being too complex for human capabilities. To improve this situation we propose complementing traditional design approaches with a design synthesis proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Although this is significant within design, it is even more so within an urban scale, as the process allows for the simultaneous output of geometrically unique morphologies from a single simulation, in which the solutions share similar attributes on a global scale, but differ considerably on the local scale. The work of Balling et al, 15 Makki et al, 16 Koenig, 17 Navarro, 18 Showkatbakhsh 19 and others in the field have demonstrated the above, in which the application of MOEAs are used as the primary approach to solve complex design problems, both in gaining a better understanding of their formulation, as well as achieving results that are driven by quantitatively measurable data sets. Where these studies have thoroughly examined the application of population based evolutionary algorithms to generate urban form, there remains the challenge of selecting viable urban solutions based on the morphological representation of the data outputted by the evolutionary simulation, in which the data set is optimised to allow for the data-driven and comparative visual analysis and selection of the outputted solution set.…”
Section: Culture and The Citymentioning
confidence: 99%
“…Although this is significant within design, it is even more so within an urban scale, as the process allows for the simultaneous output of geometrically unique morphologies from a single simulation, in which the solutions share similar attributes on a global scale, but differ considerably on the local scale. The work of Balling et al, 15 Makki et al, 16 Koenig, 17 Navarro, 18 Showkatbakhsh 19 and others in the field have demonstrated the above, in which the application of MOEAs are used as the primary approach to solve complex design problems, both in gaining a better understanding of their formulation, as well as achieving results that are driven by quantitatively measurable data sets. Where these studies have thoroughly examined the application of population based evolutionary algorithms to generate urban form, there remains the challenge of selecting viable urban solutions based on the morphological representation of the data outputted by the evolutionary simulation, in which the data set is optimised to allow for the data-driven and comparative visual analysis and selection of the outputted solution set.…”
Section: Culture and The Citymentioning
confidence: 99%
“…Other use cases in this theme include the analysis of urban change over time [BDW*08, KD19], walkability considering 3D footpath networks [SWZ21, ZSW21], simulation of radio propagation in city environments [BCC*18], enclosure assessment [KM17], urban design plans [LS13, Rei15, MKK*18, LSAG22, SD23], and the study of urban vitality [ZY18] (Figure 12 (Linked view)).…”
Section: Primary Dimensions (Why)mentioning
confidence: 99%
“…Even though certain domain‐specific papers support exploration [YNK*18,TLH*22], they mostly rely on off‐the‐shelf 3D visualization libraries, with very little effort going towards the customization of these interfaces to satisfy specific tasks. An outlier is the work by Reinhard that combines 2D and 3D visualizations for the exploration of urban planning projects [Rei15].…”
Section: Primary Dimensions (Why)mentioning
confidence: 99%
“…On the scale of district and community, design-decision-support platforms [123,124] are built to simulate interactions between buildings, plants, environmental conditions, and human activities [125]. Kirnbauer [126] integrated multiple databases into a decision support system for urban tree planting.…”
Section: Digital Tools and Databases Of Trees Used In The Building In...mentioning
confidence: 99%